Efficient sterilization using reactive oxygen species generated by a radical vapor reactor. (March 2017) - Takatsuji, Yoshiyuki; Ishikawa, Shoko; Haruyama, Tetsuya
Graphical abstract: Highlights: The ROS (singlet oxygen, hydroxyl radicals, and ozone) generation amount can be controlled with the use of different radical vapor reactor (RVR) modes. These bacteria ( E. coli and B. subtilis ) were sterilized by different RVR modes. The effective and quickly sterilization using singlet oxygen and hydroxyl radicals. Abstract: Numerous sterilization techniques using ozone have been proposed. However, singlet oxygen and hydroxyl radicals show stronger oxidation activity than ozone, and therefore exert a greater sterilization effect against microorganisms. We recently developed a radical vapor reactor (RVR) as a powerful tool for microorganism sterilization, which is based on the efficient generation and exposure of reactive oxygen species (ROS) such as singlet oxygen and hydroxyl radicals including ozone. Therefore, effective sterilization via ROS generation is expected by optimizing the RVR conditions. In this study, the generations of ROS was measured under various RVR conditions using spin-trapping electron spin resonance analysis and ozone monitoring. We demonstrated the effective sterilization of Escherichia coli and Bacillus subtilis by exposure to ozone, singlet oxygen, and hydroxyl radicals whose production levels were successfully controlled.